Palindrome‐Mediated and Replication‐Dependent Pathogenic Structural Rearrangements within the NF1 Gene. Issue 7 (21st May 2014) - Hsiao, Meng‐Chang; Piotrowski, Arkadiusz; Alexander, John; Callens, Tom; Fu, Chuanhua; Mikhail, Fady M.; Claes, Kathleen B.M.; Messiaen, Ludwine
<x xml:space="preserve">Abstract</x> In this study, we have identified five deletions and one chromosomal translocation t(14;17)(q32;q11.2) mediated by a 197‐bp long palindromic AT‐rich repeat (PATRR17) within the NF1 gene. Although several previous studies indicated a purely replication‐independent mechanism for PATRR‐mediated translocations, the PATRR17‐mediated intragenic deletions as well as the translocation are likely the result of a replication‐dependent mechanism. Furthermore, we identified the PATRR17, especially the loop of PATRR17, as a significant intragenic rearrangement hotspot within the NF1 gene. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>